Between familial imprinting and institutional regulation: Family related employment interruptions of women in Germany before and after the German reunification - Katrin Drasch (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2012)
In this paper, I examine how family related employment interruptions for women in the FRG (Federal Republic of Germany) and the GDR (German Democratic Republic) looked like in the period prior to German reunification. Furthermore, I investigate how career interruptions developed after the German reunification in the old and new states and whether a convergence of re-entry behaviour can be observed. Following research questions are addressed: Which factors are more important: attitudes towards the employment of mothers, which were transferred through socialisation in childhood and adolescence, or institutional arrangements shaped by parental leave regulations? Based on data from the IAB ALWA study ('Working and Learning in a Changing World') the results show that even twenty years after the German reunification, significant differences between women in East and West Germany are found to exist with respect to family related employment interruptions. These interruptions are subject to strong institutional control. Women who were raised in the GDR and moved to one of the old federal states after the reunification do not behave differently than West German women. This result suggests that institutional arrangements including for example also childcare availability are more important for re-entry behaviour than socialisation. However, the results must be interpreted carefully: it could be that the willingness to move of East German women is also influenced by socialisation. – – In diesem Beitrag wird der Frage nachgegangen, wie sich familienbedingte Erwerbsunterbrechungen aufgrund der Geburt von Kindern vor der Wiedervereinigung in der Bundesrepublik und der DDR gestaltet haben. Weiterhin wird untersucht, wie sich Unterbrechungen nach der Wiedervereinigung in den alten und neuen Bundesländern entwickelt haben, und ob eine Annäherung des Wiedereinstiegsverhaltens stattgefunden hat. Folgende Forschungsfragen werden gestellt: Welche Faktoren sind wichtiger: Einstellungen zur Erwerbstätigkeit von Müttern, die durch die Sozialisation in Kindheit und Jugend weitergegeben wurden oder die institutionelle Ordnung, die durch Elternzeitregelungen beeinflusst wurde? Die Ergebnisse auf Basis der Lebensverlaufsstudie Arbeiten und Lernen im Wandel (ALWA) des Instituts für Arbeitsmarkt- und Berufsforschung (IAB) zeigen, dass auch zwanzig Jahre nach der deutschen Wiedervereinigung deutliche Unterschiede zwischen Frauen in Ost- und Westdeutschland bezüglich der Dauer von familienbedingten Erwerbsunterbrechungen existieren. Familienbedingte Erwerbsunterbrechungen unterliegen einer starken institutionellen Steuerung. Frauen, die in der DDR aufgewachsen sind und nach der Wiedervereinigung in den Westen gezogen sind verhalten sich nicht anders als westdeutsche Frauen. Die deutet darauf hin, dass institutionelle Regelungen eine stärkere Bedeutung für das Wiedereinstiegsverhalten haben als Sozialisationsaspekte. Allerdings müssen die Ergebnisse mit einiger Vorsicht interpretiert werden. Es könnte sein, dass die Umzugsbereitschaft ostdeutscher Frauen ebenfalls durch die Sozialisation beeinflusst wird.
Keywords: J21; C41; 330; maternal employment; parental leave legislation; discrete-time event history analysis; Mütter; Weibliche Arbeitskräfte; Erwerbsverlauf; Berufliche Integration; Sozialisation; Elternzeit; Vergleich; Alte Bundesländer; Neue Bundesländer; Deutschland